Closure of traumatic wounds without cleaning and suturing. Issue 919 (1st May 2002) - Maharaj, D; Sharma, D; Ramdass, M; Naraynsingh, V
Abstract : Background: In less than ideal situations wounds have to be closed without extensive cleaning using sterile adhesive strips (Steristrips). This prospective analyses the efficiency of this technique and compares it to the more conventional approach. Methods: Altogether 147 lacerations were closed with sterile strips with no wound cleaning. Patients were subsequently followed up for a minimum of three months. Results: The sepsis rate in compliant patients was 1.4% with a total complication rate of 2.7%. Conclusion: This technique, while contradicting the "sacred tenets" of wound closure, is a cheap, quick, and effective alternative to routine closure of traumatic wounds in a casualty department.